2017
DOI: 10.3390/su9061019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Understory Liana Trachelospermum jasminoides on Distributions of Litterfall and Soil Organic Carbon in an Oak Forest in Central China

Abstract: Liana constitutes an important structural and functional component in many forest ecosystems and has profound impacts on forest carbon (C) cycling. However, whether and how liana regulates spatial distributions of litterfall and soil organic C are still poorly understood. To address this critical knowledge gap, we investigated litterfall composition and soil physicochemical characteristics in stands with different densities of liana (Trachelospermum jasminoides (Lindl.) Lem.). Both fresh and decomposed leaf li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…The seasonal difference of soil respiration rate after vegetation restoration is significant, and the average annual soil respiration rate after vegetation restoration is significantly higher than that of the untreated land in the red soil erosion area (Deng et al., 2019). It had shown that forest ecosystems covered with dense liana, contain higher soil respiration rate, soil organic C, and total nitrogen than those with less covered ones (Liu, Shang, Zhang, Zhang, & Luan, 2017). It was found that soil management and amendments mostly affect soil respiration rate during the most active spring and summer period of the ecosystem (Horel, Tóth, Gelybó, Dencső, & Potyó, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The seasonal difference of soil respiration rate after vegetation restoration is significant, and the average annual soil respiration rate after vegetation restoration is significantly higher than that of the untreated land in the red soil erosion area (Deng et al., 2019). It had shown that forest ecosystems covered with dense liana, contain higher soil respiration rate, soil organic C, and total nitrogen than those with less covered ones (Liu, Shang, Zhang, Zhang, & Luan, 2017). It was found that soil management and amendments mostly affect soil respiration rate during the most active spring and summer period of the ecosystem (Horel, Tóth, Gelybó, Dencső, & Potyó, 2018).…”
Section: Resultsmentioning
confidence: 99%